The Role of Cadres in Conducting Coaching for Mothers Who Have Toddler Children - Izzawati, Siti Sajida; Karwati, Lilis; Yuliani, Lulu (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
Bina Keluarga Balita (BKB) is a family welfare program aimed at increasing parents' knowledge and skills regarding child development, with the program implemented by community volunteers. This study aims to understand the role of BKB cadres as agents of change in guiding mothers with toddlers and to identify supporting and inhibiting factors. Cadres are expected to drive change in BKB activities. The research method used is qualitative with a phenomenological approach. Data collection techniques include interviews, observations, and documentation. The results show that cadres play roles in socialization, building relationships, diagnosing conditions, providing counseling, filling out Child Development Cards (KKA), using educational play tools (APE), and monitoring mothers with toddlers. Supporting factors include a focus on mothers' needs and integration with Posyandu and PAUD services. Inhibiting factors include a lack of cadres training, slow regeneration, and limited government funding. In conclusion, the role of cadres as agents of change is quite successful in improving mothers' knowledge and skills about BKB